2018
DOI: 10.15640/jsbed.v5n2a7
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Activeness and Survival of Small and Medium Scale Enterprises in Nigeria

Abstract: The study investigated the relationship between Pro-activeness and the Survival of small and medium scale enterprises (SMEs) in Port Harcourt. The cross sectional survey method was adopted. A sample size of eighty was drawn from a population of one hundred employees using the Taro Yamane formula. The questionnaire was the main instrument for data collection and data obtained was analyzed using the SPSS. Spearman's rank correlation coefficient was used to test the hypotheses. Our findings revealed a strong and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Over the years, scholars have developed an engaging interest in defining business survival and accounting for the factors that explain the survival or non-survival of firms in an environment (Geroski et al, 2009; Mata & Portugal, 2002). Amah (2017) stated that the survival of a business entails its continuity. Additionally, Geroski et al (2009) posited that growth does not differ from survival, as it can be used to explain business survival.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the years, scholars have developed an engaging interest in defining business survival and accounting for the factors that explain the survival or non-survival of firms in an environment (Geroski et al, 2009; Mata & Portugal, 2002). Amah (2017) stated that the survival of a business entails its continuity. Additionally, Geroski et al (2009) posited that growth does not differ from survival, as it can be used to explain business survival.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Entrepreneurial resilience can be defined as an entrepreneur’s ability to develop and maintain an adaptive mindset and capabilities to confront and overcome the challenges associated with new business growth and survival (Ayala & Manzano, 2014; Pathak et al, 2023). It is also the capacity of an entrepreneur to effectively respond to unforeseen disruptive changes that may occur in their business (Amah & Eshegheri, 2017; Mberi, 2018). Entrepreneurial resilience can, therefore, be viewed as a mental tool that helps an individual keep their mind, body, and spirit intact throughout a challenging journey.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as a downturn in the national economy, high prices of construction materials, poor estimation practices, delayed progress payments from clients, and non-payment of interest on late allowances have been identified as the main causes of the decline in the number of contractors (Yoo & Kwak, 2020;Adenuga et al, 2020;Ndayisenga et al, 2019;El-Kholy & Akal, 2019). Ramezeni and Papzan (2021) showed that insufficient infrastructure, poor support, economic barriers, and human resource constraints drove the deterioration of businesses (Guan & He, 2021;Kumawat & Bhatnagar, 2019;Adesua & Oladipo, 2018).…”
Section: Contributing Factors Of Business Declinementioning
confidence: 99%
“…FP influence the mission of creating new opportunities in the market and the further development of industries (Audretsch and Link, 2016;Leyden, 2016;Mazzucato, 2016). The problems of management of industrial enterprises in general and, in particular, the problems of management of their sustainable innovative development were investigated in the works (Amah, 2017;Sorokin and Novikov, 2019;Tuguskina, 2019;Usov et al, 2018;Ustinova and Sirazetdinov, 2017).…”
Section: Introductionmentioning
confidence: 99%